2020
DOI: 10.1186/s12881-020-0947-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cellular cobalamin metabolism in Gaucher disease

Abstract: Background: Gaucher disease (GD) is a lysosomal disorder caused by biallelic pathogenic mutations in the GBA1 gene that encodes beta-glucosidase (GCase), and more rarely, by a deficiency in the GCase activator, saposin C. Clinically, GD manifests with heterogeneous multiorgan involvement mainly affecting hematological, hepatic and neurological axes. This disorder is divided into three types, based on the absence (type I) or presence and severity (types II and III) of involvement of the central nervous system. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…However, studies performed on skin fibroblasts from healthy controls and from GD types I, II, and III suggested that cellular utilization of B 12 is preserved in this cell type (Basgalupp et al, 2020). This finding along with literature reports on elevated plasma biomarkers point to the need to further investigate how impaired lysosomal storage influences B 12 metabolism in different cell types as well as its partition between biological compartments (plasma versus cells).…”
Section: Introductionmentioning
confidence: 82%
“…However, studies performed on skin fibroblasts from healthy controls and from GD types I, II, and III suggested that cellular utilization of B 12 is preserved in this cell type (Basgalupp et al, 2020). This finding along with literature reports on elevated plasma biomarkers point to the need to further investigate how impaired lysosomal storage influences B 12 metabolism in different cell types as well as its partition between biological compartments (plasma versus cells).…”
Section: Introductionmentioning
confidence: 82%